Grotescul geniului şi geniul grotesc - Aluniţa Cofan (Revista de Istorie și Teorie Literară)
The following pages contain a hermeneutical analysis of the grotesque into Eugen Ionescu’s biographical study “Tragic and grotesque life of Victor Hugo”. We have here two points of view of the grotesque: the first one has a theoretical significance and the second one refers to an inside presence in narrative scenes. Deconstruction of logical methods, as well as syllogism, is pointing to the grotesque non-values: risible, clownish, horrible.